Changing seasonality of panarctic tundra vegetation in relationship to climatic variables - Bhatt, Uma S; Walker, Donald A; Raynolds, Martha K; Bieniek, Peter A; Epstein, Howard E; Comiso, Josefino C; Pinzon, Jorge E; Tucker, Compton J; Steele, Michael; Ermold, Wendy; Zhang, Jinlun (Environmental research letters, 2017)
Potential climate drivers of Arctic tundra vegetation productivity are investigated to understand recent greening and browning trends documented by maximum normalized difference vegetation index (NDVI) (MaxNDVI) and time-integrated NDVI (TI-NDVI) for 1982-2015. Over this period, summer sea ice has continued to decline while oceanic heat content has increased. The increases in summer warmth index (SWI) and NDVI have not been uniform over the satellite record. SWI increased from 1982 to the mid-1990s and remained relatively flat from 1998 onwards until a recent upturn. While MaxNDVI displays positive trends from 1982-2015, TI-NDVI increased from 1982 until 2001 and has declined since. The data for the first and second halves of the record were analyzed and compared spatially for changing trends with a focus on the growing season. Negative trends for MaxNDVI and TI-NDVI were more common during 1999-2015 compared to 1982-1998. Trend analysis within the growing season reveals that sea ice decline was larger in spring for the 1982-1998 period compared to 1999-2015, while fall sea ice decline was larger in the later period. Land surface temperature trends for the 1982-1998 growing season are positive and for 1999-2015 are positive in May-June but weakly negative in July-August. Spring biweekly NDVI trends are positive and significant for 1982-1998, consistent with increasing open water and increased available warmth in spring. MaxNDVI trends for 1999-2015 display significant negative trends in May and the first half of June. Numerous possible drivers of early growing season NDVI decline coincident with warming temperatures are discussed, including increased standing water, delayed spring snow-melt, winter thaw events, and early snow melt followed by freezing temperatures. Further research is needed to robustly identify drivers of the spring NDVI decline.